(untitled) (London Journal of Research In Management & Business, 2025)
Business Process Management platforms are vital enablers supporting the efficient optimization of global supply chains because they provide fast application development, solid process automation, and end-to-end real-time visibility. It is thus crucial to explore the development of Appian solutions specifically customized to supply chain teams, assess the natural positive side of choosing to develop solutions within a BPM-based system, and the strategic justification of investing in low-code BPM solutions across the enterprise-level Appian. The analysis based on three trusted sources only allows for the synthesis of the results. It reveals how the visual modeling interface, inbuilt robotic process automation functions, and analytics dashboards provided by Appian facilitate and simplify the core supply chain functions, such as procurement, inventory management, and logistics coordination, ensuring visible gains in cycle times, data accuracy, and decision-making agility. The facts point to the fact that the organizations embracing Appian realize its substantial manual work reduction, decreased time to markets, and speedy investment returns.